2017
DOI: 10.1590/1678-457x.05817
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ultraviolet B (UV-B) irradiation on color quality and decay rate of Capia pepper during postharvest storage

Abstract: The current study demonstrates that the ultraviolet-B (UV-B) irradiation not only helps in improvement of the red color of the peppers but also reduces their rate of decay. The Capia peppers were harvested at their full red ripe stage and subjected to the UV-B treatment at doses 4.46 kJ m -2 (UV-B 15) and 8.93 kJ m -2 (UV-B 30). Post irradiation, the peppers were packaged and stored at 5 ± 1 °C temperature with 90-95% RH for 49 days. The UV-B treated group showed lower L* values, but higher a* and h° values as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…Regarding colour variations (∆E), this effect is similar to results reported by Kasim and Kasim, [31], who showed that low UV-B doses (4.46 kJ m -2 ) did not affect the colour development during 6 d at 7 • C. As observed, TSS has been related to MI and, particularly in red peppers, these two parameters have also been associated with colour development [32], which can also be contrasted with our present results. Moreover, sensory quality values can be related to the overall marketability, which has been previously reported to be increased after applying blue and red LEDs [33] or UV low doses [31,34].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding colour variations (∆E), this effect is similar to results reported by Kasim and Kasim, [31], who showed that low UV-B doses (4.46 kJ m -2 ) did not affect the colour development during 6 d at 7 • C. As observed, TSS has been related to MI and, particularly in red peppers, these two parameters have also been associated with colour development [32], which can also be contrasted with our present results. Moreover, sensory quality values can be related to the overall marketability, which has been previously reported to be increased after applying blue and red LEDs [33] or UV low doses [31,34].…”
Section: Discussionsupporting
confidence: 90%
“…As total phenolic and flavonoid contents have been directly related to the antioxidant capacity of these fruit [5], the TAC was positively affected by FL + FL and FL + BR LED photoperiods regarding FL + D, which was also highly remarkable after 6 d at 7 • C + 4 d 20 • C. Values obtained can be comparable to previous studies in which UV-B increased the TAC according to DPPH values [31], and this effect has also been shown in UV-C-treated red peppers [35]. Moreover, an increase of the TAC measured by FRAP in fresh-cut red peppers for 11 d at 7 • C has also been reported for the application of 8 h blue and red LEDs separately [33].…”
Section: Discussionsupporting
confidence: 86%
“…Carotenoid pigments provide Red and Orange capsicum fruits with their visual appeal and reflect the maturity of ripened fruits. Since capsicum fruit are non-climacteric and picked ripe, fruit colour does not usually change after harvest [ 42 ]. Carotenoid biosynthesis can be regulated by the light environment leading to changes in fruit colour [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Where Wi and Ws show the weight of samples at initial and at a sampling period, respectively (Kasım and Kasım, 2018).…”
Section: Weight Lossmentioning
confidence: 99%